The Dangers of Building Your Own Python Applications: False-Positives, Unknown Publishers, and Code Licensing - Corey Schmidt (Code4Lib Journal)
Making Python applications is hard, but not always in the way you expect. In an effort to simplify our archival workflows, I set out to discover how to make standalone desktop applications for our archivists and processors to make frequently used workflows easier and more intuitive. Coming from an archivists’ background with some Python knowledge, I learned how to code things like Graphical User Interfaces (GUIs), to create executable (binary) files, and to generate software installers for Windows. Navigating anti-virus software flagging your files as malware, Microsoft Windows throwing warning messages about downloading software from unknown publishers (rightly so), and disentangling licensing changes to a previously freely-available Python library all posed unexpected hurdles that I’m still grappling with. In this article, I will share my journey of creating, distributing, and dealing with the aftereffects of making Python-based applications for our users and provide advice on what to look out for if you’re looking to do something similar.